日本人の耐力測定結果に関する考察 : 健常者を対象とした測定結果に基づく報告 - 宮野, 道雄; 久本, 誠一; 樋口, 雅俊; 岡田, 明 (日本生理人類学会誌, 2008)
The purpose of this study was to develop an overview of the physical fitness of Japanese people, ranging from the young to the elderly, based on data regarding the physical characteristics of workers obtained by the National Institute of Technology and Evaluation (NITE), and to assess the relationship between their physical fitness and extremity joint torque and between their physical fitness and lifestyle. The data used in this study were measurements of the physical fitness of 1000 Japanese workers between 2001 and 2002. The parameters measured were grip strength, vertical jump, trunk flexion seated, jump reaction time, single-leg standing time with eyes closed, and limb joint torque, and replies to a questionnaire on lifestyle and exercise history were also used. The results revealed two tendencies: a tendency for the single-standing time with eyes closed values to decrease steadily with age, and a tendency for the grip strength, vertical jump, and jump reaction time values to start decreasing at a particular generation (grip strength and jump reaction time: in there forties to sixties, vertical jump: in their forties to sixties, in both gender). In addition, multiple regression analyses were carried out on the relationship between age and physical fitness and between age and limb joint torque. The results showed that physical fitness except trunk flexion seated tended to be greatly affected by age, and that grip strength tended to be affected by maximum voluntary contraction of the upper limbs. The results of a multiple regression analysis of the responses to the lifestyle questionnaire and the subjects' physical fitness characteristics revealed that grip strength, trunk flexion seated, vertical jump, and single-leg standing time with eyes closed tended to be affected by lifestyle.